Analysis of influencing factors for prognosis of patients with ventricular septal perforation: A single-center retrospective study - Ming-Xuan Duan; Xi Zhao; Shao-Lin Li; Jun-Zhong Tao; Bo-Yan Li; Xin-Guo Meng; Dong-Pu Dai; Yan-Yu Lu; Zhen-Zhen Yue; Yang Du; Zi-Ao Rui; Shuo Pang; et al. (Frontiers in Cardiovascular Medicine, 2022)
BackgroundVentricular septal rupture (VSR) is a type of cardiac rupture, usually complicated by acute myocardial infarction (AMI), with a high mortality rate and often poor prognosis. The aim of our study was to investigate the factors influencing the long-term prognosis of patients with VSR from different aspects, comparing the evaluation performance of the Gensini score, Sequential Organ Failure Assessment (SOFA) score and European Heart Surgery Risk Assessment System II (EuroSCORE II) score systems.MethodsThis study retrospectively enrolled 188 patients with VSR between Dec 9, 2011 and Nov 21, 2021at the First Affiliated Hospital of Zhengzhou University. All patients were followed up until Jan 27, 2022 for clinical data, angiographic characteristics, echocardiogram outcomes, intraoperative, postoperative characteristics and major adverse cardiac events (MACEs) (30-day mortality, cardiac readmission). Cox proportional hazard regression analysis was used to explore the predictors of long-term mortality.ResultsThe median age of 188 VSR patients was 66.2 ± 9.1 years and 97 (51.6%) were males, and there were 103 (54.8%) patients in the medication group, 34 (18.1%) patients in the percutaneous transcatheter closure (TCC) group, and 51 (27.1%) patients in the surgical repair group. The average follow-up time was 857.4 days. The long-term mortality of the medically managed group, the percutaneous TCC group, and the surgical repair group was 94.2, 32.4, and 35.3%, respectively. Whether combined with cardiogenic shock (OR 0.023, 95% CI 0.001–0.054, P = 0.019), NT-pro BNP level (OR 0.027, 95% CI 0.002–0.34, P = 0.005), EuroSCORE II (OR 0.530, 95% CI 0.305–0.918, P = 0.024) and therapy group (OR 3.518, 95% CI 1.079–11.463, P = 0.037) were independently associated with long-term mortality in patients with VSR, and this seems to be independent of the therapy group. The mortality rate of surgical repair after 2 weeks of VSR was much lower than within 2 weeks (P = 0.025). The cut-off point of EuroSCORE II was determined to be 14, and there were statistically significant differences between the EuroSCORE II < 14 group and EuroSCORE II≥14 group (HR = 0.2596, 95%CI: 0.1800–0.3744, Logrank P < 0.001).ConclusionPatients with AMI combined with VSR have a poor prognosis if not treated surgically, surgical repair after 2 weeks of VSR is a better time. In addition, EuroSCORE II can be used as a scoring system to assess the prognosis of patients with VSR.